ADP‐ribosylation of histone variant H2AX promotes base excision repair. (2nd December 2020) - Chen, Qian; Bian, Chunjing; Wang, Xin; Liu, Xiuhua; Ahmad Kassab, Muzaffer; Yu, Yonghao; Yu, Xiaochun
Abstract: Optimal DNA damage response is associated with ADP‐ribosylation of histones. However, the underlying molecular mechanism of DNA damage‐induced histone ADP‐ribosylation remains elusive. Herein, using unbiased mass spectrometry, we identify that glutamate residue 141 (E141) of variant histone H2AX is ADP‐ribosylated following oxidative DNA damage. In‐depth studies performed with wild‐type H2AX and the ADP‐ribosylation‐deficient E141A mutant suggest that H2AX ADP‐ribosylation plays a critical role in base excision repair (BER). Mechanistically, ADP‐ribosylation on E141 mediates the recruitment of Neil3 glycosylase to the sites of DNA damage for BER. Moreover, loss of this ADP‐ribosylation enhances serine‐139 phosphorylation of H2AX (γH2AX) upon oxidative DNA damage and erroneously causes the accumulation of DNA double‐strand break (DSB) response factors. Taken together, these results reveal that H2AX ADP‐ribosylation not only facilitates BER repair, but also suppresses the γH2AX‐mediated DSB response. Synopsis: The role of histone ADP‐ribosylation after DNA damage has remained elusive. Here, ADP‐ribosylation of histone variant H2AX on a specific residue upon oxidative damage is found to not only promote base excision repair (BER), but to also suppress γH2AX‐associated DNA double‐strand break (DSB) responses. Glutamate residue 141 (E141) of histone H2AX is ADP‐ribosylated following oxidative DNA damage. ADP‐ribosylation on E141 mediates recruitment of the BER glycosylase Neil3 to the sites of oxidative damage. H2AX E141A mutation abolishes ADP‐ribosylation and enhances serine‐139 phosphorylation to create γH2AX upon oxidative damage. Oxidative damage‐induced γH2AX formation in H2AX‐E141A mutants causes erroneous accumulation of DSB response factors. Abstract : H2AX ADP‐ribosylation upon oxidative DNA damage not only promotes recruitment of BER glycosylase Neil3, but also suppresses γH2AX formation and associated double‐strand break response signaling.